Integration of Islamic Values In The Supervision of School Principal Education In Improving Teacher Performance In Madrasah Aliyah Muhammadiyah Datarang Kabupaten Gowa - Ferdinan Ferdinan; Hj. Sumiati; Mumtahanah Mumtahanah (Asian Journal of Social and Humanities, 2023)
Efforts to improve teacher performance can be done through educational supervision carried out by school principals using an Islamic values approach in order to provide assistance and guidance to teachers through supervision activities. Guiding and providing assistance to teachers is an Islamic teaching that has existed for a long time and was exemplified by the Prophet SAW to the companions. The approach used in implementing educational supervision to improve teacher performance is based on Islamic values. The provision of supervision must be adjusted to the prototype of the teacher. Supervision must be done wisely, as written in QS. Al-Nahl/16:125. This research is a combination research (mixed methods) using sequential exploratory design method. In this model, the initial stage involves collecting quantitative data which is then complemented by qualitative data analysis. This combination of data serves to link the results of the first stage of research (quantitative data) with the next stage (qualitative data). This study aims to describe the integration of Islamic values in the implementation of educational supervision by the principal at the Muhammadiyah School in Gowa Regency. The integrated values include ihsan, sincerity, exemplary, and tajdid. This study provides an overview of the implementation of the integration of Islamic values and Kemuhammadiyahan in the implementation of educational supervision by school principals at MA Muhammadiyah Datarang, Gowa Regency. This research focuses on four aspects: ihsan, sincerity, exemplary, and tajdid. The results showed that the implementation of supervision at MA Muhammadiyah Datarang reached a high category, indicating that aspects of Islamic values in Supervision had run very well.